Leibniz on Maimonides' Guide of the Perplexed: A New English Translation - Dal Bo, Federico (Jewish studies quarterly, 2024)
Sometime between 1677 and 1691, Gottfried Wilhelm Leibniz read Johann Buxtorf's Latin translation of Maimonides' Guide of the Perplexed and made a series of personal notes in Latin, including relevant passages from the Guide, as well as philosophical and theological observations. This is a new English translation of this work, with philological and historical notes based on the 2006 edition of Leibniz's Complete Works.